Pensions and Depression: Gender-Disaggregated Evidence from the Elderly Poor in India - Amanda Guimbeau; Nidhiya Menon (Institute of Labor Economics (IZA), 2024)
We leverage the expansion of the National Social Assistance Program (NSAP) in India in 2006 to estimate the impact of access to public pensions on three measures of depression for the elderly in below poverty line households, using a regression discontinuity design based on age-eligibility cutoffs. We focus on India given that it is the largest lower-middle-income country in terms of population, has limited welfare safety nets, and relatively large proportions of disadvantaged people with mental health vulnerabilities. We find that becoming eligible for public pensions reduces the likelihood that the elderly poor are depressed. In particular, the intent-to-treat estimate is a 10.1 percentage point decline in the broadest measure of depression. Our gender-specific analyses reveal heterogeneous impacts across demographic groups. More specifically, widowed populations, the majority of whom are elderly poor women, gain the most. Our investigation into the underlying mechanisms reveals that pension eligibility improves mental health through decreased labor market participation, increased healthcare utilization, improved lifestyle choices, enhanced life satisfaction and greater control over resources. Our results offer insights for shaping effective social assistance policies aimed at raising the welfare of the most at-risk populations in resource-constrained contexts.
Keywords: H55; I12; I18; I38; J14; 330; pension eligibility; depression; mental health; elderly populations; gender; poor; widowed; India